2009
DOI: 10.1063/1.3149387
|View full text |Cite
|
Sign up to set email alerts
|

Computation of potential energy surfaces with the multireference correlation consistent composite approach

Abstract: A multireference composite method that is based on the correlation consistent Composite Approach (ccCA) is introduced. The developed approach, multireference ccCA, has been utilized to compute the potential energy surfaces (PESs) of N(2) and C(2), which provide rigorous tests for multireference composite methods due to the large multireference character that must be correctly described as the molecules dissociate. As well, PESs provide a stringent test of a composite method because all components of the method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 95 publications
0
35
0
Order By: Relevance
“…59 This formalism has been utilized recently by Mintz et al to study the potential energy surfaces of C 2 and N 2 and resulted in good agreement for their reaction coordinates, which are particularly multireference in the vicinity of the dissociation asymptote. 60 Due to the size of the copper nitrene system and the computational demand of the AQCC calculation, the active space chosen for all MR calculations was four electrons in five orbitals. Previous calculations by Dinescu et al on copper-nitrene complexes indicated that CASSCF active spaces of this size were suitable for modeling the different low-energy electronic states.…”
Section: Methodsmentioning
confidence: 99%
“…59 This formalism has been utilized recently by Mintz et al to study the potential energy surfaces of C 2 and N 2 and resulted in good agreement for their reaction coordinates, which are particularly multireference in the vicinity of the dissociation asymptote. 60 Due to the size of the copper nitrene system and the computational demand of the AQCC calculation, the active space chosen for all MR calculations was four electrons in five orbitals. Previous calculations by Dinescu et al on copper-nitrene complexes indicated that CASSCF active spaces of this size were suitable for modeling the different low-energy electronic states.…”
Section: Methodsmentioning
confidence: 99%
“…35 Along the dissociation path, this core contribution changes however by rather small amounts compared to the valence correlation changes. 39,43 Moreover, while Dunning's valence correlation-consistent cc-pVXZ basis sets 44 were appropriate for the recovery of the valence correlation energy, the more elaborate cc-pCVXZ core-valence basis sets of Dunning and co-workers 45 must be used to calculate core correlation effects. 33 The method must be based though on a multiconfigurational reference function that is capable of properly representing the dissociation without deterioration at stretched geometries.…”
Section: A Correlation Energy Contributions Involving Core Electronsmentioning
confidence: 99%
“…[4][5][6][7]11 Recently, Mintz et al 12 have applied the multireference ccCA method 13 to compute the potential energy curves of N 2 and C 2 ; they obtained errors of ∼0.06 pm for the bond lengths and ∼2 cm −1 for the harmonic frequencies.…”
Section: Introductionmentioning
confidence: 99%